Inoculation of corn silage with Lactobacillus plantarum and Bacillus subtilis associated with amylolytic enzyme supply at feeding. 1. Feed intake, apparent digestibility, and microbial protein synthesis in wethers - Lara, Erika C. [UNESP]; Bragiato, Uly C. [UNESP]; Rabelo, Carlos H.S. [UNESP]; Messana, Juliana D. [UNESP]; Reis, Ricardo A. [UNESP] (Elsevier, 2018)
The current study aimed to investigate the effects of corn silage inoculation and dietary supplementation with amylolytic enzymes, and their interactions, on feed intake, apparent digestibility, and microbial protein synthesis in wethers. Whole-crop corn forage was ensiled either with water (untreated) or with Lactobacillus plantarum MA 18/5U at 1 × 105 cfu/g fresh forage combined with Bacillus subtilis AT553098 at 1 × 105 cfu/g fresh forage (inoculated). Eight ruminally cannulated Dorper × Santa Inês crossbred wethers were used in a double 4 × 4 Latin square design. Wethers were assigned to one of four diets, as follows: 1) untreated corn silage with no amylolytic enzyme supply (US-NE); 2) untreated corn silage with amylolytic enzyme supply (US-WE); 3) inoculated corn silage with no amylolytic enzyme supply (IS-NE); and 4) inoculated corn silage with amylolytic enzyme supply (IS-WE). α-Amylase (602 dextrinizing units/kg of dry matter (DM)) was supplied to the wethers at total mixed ration delivery. Dietary supplementation with amylolytic enzyme increased (P = 0.045) DM and starch (P = 0.014) intake in wethers fed the US diet (+245 and +136 g/d, respectively), but not in those fed the IS diet. Inoculation of corn silage (P = 0.026) improved organic matter (OM), crude protein (CP), neutral detergent fiber (aNDFom), and gross energy (GE) digestibility by 5.3%, 11.5%, 25.8%, and 7.1%, respectively. Likewise, enzyme supply increased (P = 0.042) the apparent digestibility of DM, OM, CP, aNDFom, and GE by 5.1%, 4.7%, 9.4%, 20.7%, and 6.2%, respectively. Enzyme supply increased the molar proportion of propionic acid (P = 0.002; 24.1 vs. 19.6 mM / 100 mM) in wethers fed the US diet, but not in those fed the IS diet. Enzyme supply decreased microbial N synthesis (P = 0.025; 6.33 vs. 8.05 g/d) when the wethers were fed the IS diet, but not the US diet. In conclusion, despite the improved OM digestibility, dietary supplementation with amylolytic enzyme yielded inconsistent results with respect to feed intake and microbial protein synthesis in wethers fed diets differing in the use of silage inoculant.
Keywords: Amylase; Bacterial inoculant; Digestibility; Ruminal fermentation; Starch